Multi-level factors influencing HIV risk behaviors and oral PrEP use among Black and Latino men with heterosexual contact in New York City. - Ohshue S Gatanaga; Dalila Victoria Lanza; Robert A Pitts; Ronald S Braithwaite; Sahnah Lim (PLoS ONE, 2025)
Background New HIV infections are increasing among heterosexual Black and Latino populations in the United States, yet little is known about the shared characteristics of HIV risk behaviors and oral PrEP use among these populations. This study sought to understand factors influencing HIV risk behaviors and oral PrEP use among low income, limited English proficient (LEP), Black and Latino men with heterosexual contact in New York City (NYC). Methods Sixteen Black and Latino cisgender men with heterosexual contact and indication for PrEP were recruited from an urban safety net hospital in NYC between 2021 and 2022. In-depth interviews were conducted with participants in English and Spanish. Thematic content analysis was conducted. Results Participants described multi-faceted experiences around PrEP use informed by HIV stigma, limited understanding of PrEP, and PrEP attitudes from participants and their social networks. Participants' HIV risk behaviors were informed by sexual decision making rooted in hegemonic masculinity, trust, and perceived HIV and STI susceptibility. Participants disclosed the mixed and diverse nature of their sexual networks (i.e., cisgender women, gay men, transgender women, and sex workers). Among LEP Spanish-speaking participants, HIV risk behaviors were contextually embedded in histories of sexual or physical abuse, child labor, and/or substance use problems. Conclusions Our results call for interventions that improve sexual health knowledge, reduce stigma, and foster open discussions around sexual networks. Combined, these interventions may contribute to more accurate understanding of HIV risk behaviors and reduction of HIV transmission, especially among communities impacted by sociopolitical disenfranchisement such as LEP Spanish-speakers.